2011
DOI: 10.3348/kjr.2011.12.1.89
|View full text |Cite
|
Sign up to set email alerts
|

Combined Fluoroscopy- and CT-Guided Transthoracic Needle Biopsy Using a C-Arm Cone-Beam CT System: Comparison with Fluoroscopy-Guided Biopsy

Abstract: ObjectiveThe aim of this study was to evaluate the usefulness of combined fluoroscopy- and CT-guided transthoracic needle biopsy (FC-TNB) using a cone beam CT system in comparison to fluoroscopy-guided TNB (F-TNB).Materials and MethodsWe retrospectively evaluated 74 FC-TNB cases (group A) and 97 F-TNB cases (group B) to compare their respective diagnostic accuracies according to the size and depth of the lesion, as well as complications, procedure time, and radiation dose.ResultsThe sensitivity for malignancy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
2
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 24 publications
4
30
2
4
Order By: Relevance
“…This is comparable to published literature from Eberhardt and colleagues showing a sensitivity of 70,3% for invisible iSPNs diagnosed with the help of minprobe EBUS under fluoroscopy 14. In the case where the iSPN cannot be reached intrabronchially, the iguide needle guidance for transthoracic approach should be used 20,21. Comparable accuracy between the DynaCT guided transthoracic approach21 (93%) and the DynaCT guided endobronchial approach in centered biopsies (94%) has been observed in our study.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This is comparable to published literature from Eberhardt and colleagues showing a sensitivity of 70,3% for invisible iSPNs diagnosed with the help of minprobe EBUS under fluoroscopy 14. In the case where the iSPN cannot be reached intrabronchially, the iguide needle guidance for transthoracic approach should be used 20,21. Comparable accuracy between the DynaCT guided transthoracic approach21 (93%) and the DynaCT guided endobronchial approach in centered biopsies (94%) has been observed in our study.…”
Section: Discussionsupporting
confidence: 79%
“…In the case where the iSPN cannot be reached intrabronchially, the iguide needle guidance for transthoracic approach should be used 20,21. Comparable accuracy between the DynaCT guided transthoracic approach21 (93%) and the DynaCT guided endobronchial approach in centered biopsies (94%) has been observed in our study. Of notice is the fact that in our study only in 6% a pneumothorax occured vs. 14% resp.…”
Section: Discussionsupporting
confidence: 68%
“…Initial experiences suggested that CBCT-guided TNB could be a useful, safe and accurate procedure for diagnosis of CBCT cone-beam computed tomography, CT computed tomography, PPV positive predictive value, NPV negative predictive value, SD standard deviation a Analysis made in the 103 biopsies for which final pathologic diagnosis was available (of 20 missing, 10 were inadequate samples and 10 were indeterminate/benign lesions currently on follow-up) b Analysis made in the 179 biopsies for which final pathologic diagnosis was available (of 22 missing, 18 were inadequate samples and four were indeterminate/benign lesions currently on follow-up) indeterminate lung nodules, with possible advantages over fluoro-CT-guided biopsy [10,[12][13][14]19]. It is well known that limited access due to a closed CT gantry increases the difficulty of TNB and increases radiation exposure for the operator, whereas the greater working space provided by the C-arm cone-beam system facilitates needle placement and speeds up the procedure [12,20].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years a new, real-time needle guidance technique using C-arm cone-beam CT (hereafter CBCT) was developed that can be used to visualize under fluoroscopic guidance the needle trajectory from skin to target pulmonary lesions during interventional radiology procedures [6][7][8][9][10]. It has been suggested that the CBCT system, compared to fluoro-CT, facilitates the needle biopsy procedure and likely reduces radiation exposure of patient and operator [11][12][13][14][15]; however a direct comparison with evaluation of the advantages of CBCT over conventional fluoro-CT biopsy is not currently available [15]. In this study we aimed to compare the performance of CBCT-guided and fluoro-CT-guided TNB for diagnosis of malignancy of indeterminate lung nodules, and to assess the radiation exposure with the two procedures.…”
Section: Introductionmentioning
confidence: 99%
“…As many as 29% of patients whose conditions were not diagnosed as malignant on trans-thoracic needle biopsy were ultimately found to have carcinoma (5). According to literature reports, the sensitivity and specificity of lung biopsy are separately 86% and 98.8% while its sensitivity and specificity can reach 91%, 94% by combining with perspective and CT guidance (7,8). The accuracy of puncture is evidently related to the location, depth and size of lesions; for nodules <2 cm, the total diagnosis accuracy of CT-guided puncture is about 77.2% (9); while for Figure 2A, showing an expansible lesion within a rib; as the patient was asymptomatic with normal blood parameters, the consensus was to follow the lesion with a roentgenogram.…”
Section: Review Articlementioning
confidence: 99%